2021
DOI: 10.1039/d1sc02503a
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox-catalyzed aminofluorosulfonylation of unactivated olefins

Abstract: The development of efficient approaches to access sulfonyl fluorides is of great significance because of the widespread applications of this structural motif in many areas, among which the emerging Sulfur...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 82 publications
0
25
0
Order By: Relevance
“…Very recently, benzimidazolium-based reagents (Figure A) were simultaneously uncovered by Wang and Liao , group independently to serve as sulfonyl fluoride radical precursors by photoredox catalysis, enabling the synthesis of alkenyl sulfonyl fluorides and β-alkoxy sulfonyl fluorides, among other functionalities. Weng and co-workers formed carbon-centered radicals by proton-coupled electron transfer (PCET) to amides and intramolecular 5- exo -trig cyclization with alkenes or by energy transfer (EnT)-mediated decarboxylation of oxime esters . These can then be trapped by SO 2 and “F + ” equivalents to enable the intramolecular 1,2-amido-fluorosulfonylation of alkenes and decarboxylative fluorosulfonylation of oxime esters, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, benzimidazolium-based reagents (Figure A) were simultaneously uncovered by Wang and Liao , group independently to serve as sulfonyl fluoride radical precursors by photoredox catalysis, enabling the synthesis of alkenyl sulfonyl fluorides and β-alkoxy sulfonyl fluorides, among other functionalities. Weng and co-workers formed carbon-centered radicals by proton-coupled electron transfer (PCET) to amides and intramolecular 5- exo -trig cyclization with alkenes or by energy transfer (EnT)-mediated decarboxylation of oxime esters . These can then be trapped by SO 2 and “F + ” equivalents to enable the intramolecular 1,2-amido-fluorosulfonylation of alkenes and decarboxylative fluorosulfonylation of oxime esters, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…With the ability to synthesize pyrrolidinone-, oxazolidinone-, and imidazolidinone-containing sulfonyl fluorides, Zhong et al reported a straightforward strategy to form aliphatic sulfonyl fluorides in a multicomponent approach. 308 A PCET mechanism is responsible for the generation of an amidyl radical that initiates the 5-exo-trig cyclization. DABSO and N-fluorobenzenesulfonimide (NFSI) are respectively the SO 2 surrogate and the fluorine source.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Sulfonyl fluorides as the most widely used connective hubs of SuFEx click reaction have attracted enormous attention and find widespread applications in the fields of chemical biology 2 6 , drug discovery 7 11 and materials science 12 16 . Methods have been developed for rapid construction of sulfonyl fluoride moiety, including the chloride-fluoride exchange of sulfonyl chlorides 17 19 , SO 2 insertion/fluorination 20 23 , electrophilic fluorination of thiols and anodic oxidative fluorination 24 27 . Compared with the above mentioned S-F bond formation, direct fluorosulfonylation would provide a concise and redox economic approach for C-SO 2 F bond formation.…”
Section: Introductionmentioning
confidence: 99%